Normal expression of IFN-gammaR in four patients with uncommon mycobacterial infection phenotypes - Rugeles,M.T. (2004)
Several primary immunodeficiency diseases affecting the interleukin 12/interferon gamma (IFN-gamma) pathway have been identified, most of them characterized by recurrent and protracted infections produced by intracellular microorganisms, particularly by several species of mycobacteria. In the present study we analyzed the expression of IFN-gamma receptor (IFN-gammaR) and signal transducer and activator of transcription 1 (STAT-1) in 4 children with Mycobacterium tuberculosis infection of uncommon clinical presentation. These molecules were evaluated by flow cytometry and Western blotting in B cells transformed with Epstein-Barr virus and mutations were scanned by single-strand conformational polymorphisms and DNA sequencing. The expression of IFN-gammaR1 was normal in all 4 patients. The genetic analysis of IFN-gammaR1 and IFN-gammaR2 coding sequences did not reveal any mutation. The expression of the STAT-1 molecule was similar in patients and healthy controls; however, when the phosphorylation of this transcription factor in response to IFN-gamma activation was evaluated by Western blot, a significant lower signal was evident in one patient. These data indicate that there are no alterations in the expression or function of the IFN-gammaR chains in these patients. However, the low level of STAT-1 phosphorylation found in one of these patients might be explained by a defect in one of the molecules involved in the signal transduction pathway after IFN-gamma interacts with its receptor. In the other three patients the inability to eliminate the mycobacteria may be due to a defect in another effector mechanism of the mononuclear phagocytes.